Enhancing students' reflective thinking skills through Problem-Oriented Project-Based Learning (POPBL) with PEKERTI worksheet - Nur Suhaiba Sinusi; I. Ibrohim; Sofia Ery Rahayu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Reflective thinking skills are vital for 21st-century life skills. This study examines the effectiveness of the Problem-Oriented Project-Based Learning (POPBL) model combined with the PEKERTI Worksheet in improving the reflective thinking skills of eighth-grade students at Junior High School 2 Alla, Enrekang, South Sulawesi. POPBL emphasizes real-world problem-solving, while the PEKERTI Worksheet—focusing on questions (PErtanyaan), essential concepts (Konsep Esensial), action plans (Rencana Tindakan), and initiatives (Inisatif)—enhances the learning process. Using a quasi-experimental design with a non-equivalent control group, the study involved 75 students divided into three groups. Data were collected via observations, questionnaires, and tests, and analyzed using ANCOVA. Results showed significantly higher reflective thinking skills in the POPBL group using the PEKERTI Worksheet compared to the POPBL-only and conventional learning groups (p = 0.000). These findings suggest that integrating POPBL with the PEKERTI Worksheet effectively supports the education curriculum in Indonesia and develops essential life skills in junior high school students.